Deep profiling of multiple ischemic lesions in a large, multi-center cohort: Frequency, spatial distribution, and associations to clinical characteristics - Bonkhoff, Anna K.; Ullberg, Teresa; Bretzner, Martin; Hong, Sungmin; Schirmer, Markus D.; Regenhardt, Robert W.; Donahue, Kathleen L.; Nardin, Marco J.; Dalca, Adrian V.; Giese, Anne-Katrin; Etherton, Mark R.; Hancock, Brandon L.; et al. (Frontiers in Neuroscience, 2022)
Background and Purpose: A substantial number of patients with acute ischemic stroke (AIS) experience multiple acute lesions (MAL). We here aimed to scrutinize MAL in a large, radiologically deep-phenotyped cohort. Methods: Analyses relied upon imaging and clinical data from the international MRI-GENIE study. The initial step featured the systematic evaluation of occurrences of MAL within one and several vascular supply territories. Associations between MAL and important imaging and clinical characteristics were subsequently determined. The interaction effect between single and multiple lesion status and lesion volume was estimated by means of Bayesian hierarchical regression modeling for both stroke severity and functional outcome. Results: We analyzed 2,466 patients [age=63.4±14.8, 39%women], 49.7% of which presented with a single lesion. Another 37.4% experienced MAL in a single vascular territory, while 12.9% featured lesions in multiple vascular territories. Within most territories, MAL occurred as frequently as single lesions (ratio ~1:1). Only the brainstem region comprised fewer patients with MAL (ratio 1:4). Patients with MAL presented with a significantly higher lesion volume and acute NIHSS (7.7ml vs. 1.7ml and 4 vs. 3, pFDR<0.001). In contrast, patients with a single lesion were characterized by a significantly higher WMH burden (6.1ml vs. 5.3ml, pFDR=0.048). Functional outcome did not differ significantly between patients with single versus multiple lesions. Bayesian analyses suggested that the association between lesion volume and stroke severity between single and multiple lesions was the same in case of anterior circulation stroke. In case of posterior circulation stroke, lesion volume was linked to a higher NIHSS only among those with MAL. Conclusions: Multiple lesions, especially those within one vascular territory, occurred more frequently than previously reported. Overall, multiple lesions were distinctly linked to a higher acute stroke severity, a higher total DWI lesion volume and a lower WMH lesion volume. In posterior circulation stroke, lesion volume was linked to a higher stroke severity in multiple lesions only.